In vitro dynamic digestion of model infant formulae containing lactoferrin and medium chain triacylglycerols. (September 2021) - de Figueiredo Furtado, Guilherme; Ménard, Olivia; Yu, Xiaoxi; Ossemond, Jordane; Henry, Gwénaële; Jardin, Julien; Briard-Bion, Valérie; Deglaire, Amélie; Hubinger, Miriam Dupas; Dupont, Didier
Abstract: Four different model infant formulae were compared under simulated conditions of the infant gastrointestinal tract using an in vitro dynamic digestion protocol. These formulae were based on whey protein isolate, whey protein isolate + lactoferrin, long chain triacylglycerols or long + medium chain triacylglycerols. In each of the four cases, the influence of protein and lipid composition on their subsequent structural disintegration, proteolysis and lipolysis during digestion was investigated. Structural characterization of the four types of infant formulae was done before and during simulated digestion using confocal microscopy and laser light scattering methods. Proteolysis was followed using molecular weight distribution methodology, primary amine quantification, amino acid bioaccessibility and peptide analyses. Lipolysis was determined by gas chromatography. During gastric digestion, the structure of infant formulae based on lactoferrin was barely affected by the physicochemical conditions in the gastric chamber and all the protein fractions were found to be resistant to gastric proteolysis, except for α-lactalbumin. The degree of lipolysis within the gastric and intestinal phase was influenced by the lipid composition, noting that those formulae containing medium chain triacylglycerols exhibited a higher extent of lipolysis. These results are relevant for the development of formulae enriched with functional ingredients that may provide bioactive peptides and faster energy delivery to the newborn baby. Graphical abstract: Image 1 Highlights: Lactoferrin addition resulted in more resistant structures to gastric conditions. All the proteins were rapidly hydrolyzed during intestinal digestion. Lipid composition did not alter protein hydrolysis. Lactoferrin did not influence lipolysis. Infant formulae based on medium chain triacylglycerols exhibited higher lipolysis.